Stanovení anti-Müllerova hormonu u žen - Kučera, R; Topolčan, O; Rumpíková, T; Rumpík, D; Dostál, J (Ceska gynekologie, 2013)
Anti-Müllerian hormone (AMH) is a glycoprotein and belongs to the TGF-β growth factors family. Our review describes the method of AMH determination in serum and follicular fluid. The reference values and changes in AMH levels during a womans life are also discussed. In addition, it is also presented the relationship between AMH, obesity, smoking and use of hormonal contraceptives. The focus of the work is the importance of the determination of AMH in clinical practice. In assisted reproduction has become its determination one of the tools to detect ovarian reserve. It helps not only predict reduced response to stimulation with gonadotropins but also the risk of the ovarian hyperstimulation syndrome. Benefits of the ovarian reserve detection using AMH serum levels are discussed in comparison with the antral follicle count (AFC) determined by ultrasound. Several clinical indications of AMH determination are mentioned in the next section. These are primarily the polycystic ovary syndrome (PCOS), which is a great challenge not only for the AMH testing, but there is an open space for further interdisciplinary cooperation. Endometriosis has no direct effect on ovarian reserve and AMH levels in serum. AMH is very sensitive tumor marker in the diagnostics and monitoring of ovarian granulosa cells tumors. Treatment of cancer disease burdens entire body, including healthy cells. Ovarian follicles are very sensitive to chemotherapy and radiation. AMH is a good predictor of ovarian reserve damage during radio- and chemotherapy.
Keywords: Smoking; folikulární tekutina; Endometriosis; obezita; nemoci ovaria; Follicular Fluid; lidé; Female; antimülleriánský hormon; ženské pohlaví; endometrióza; Anti-Mullerian Hormone; Obesity; Humans; kouření; Ovarian Diseases